Strategi Manajemen Operasional Dalam Mengoptimalkan Efisiensi Proses Produksi: Penelitian - Nurul Aisyah Hasan; Nur Faadhillah Jufri; Serlin Serang; Ramlawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Economic development is an integral part of national development, in which operations management has become a significant research topic influencing both academics and industry professionals in the manufacturing and industrial sectors. Effective operations management within a company increases the likelihood of organizational sustainability and competitiveness. This paper aims to propose several strategic recommendations that can be implemented to address operational process challenges within firms. The study employs a qualitative descriptive method to illustrate existing conditions and operational issues. The findings indicate that companies seeking to improve operational efficiency can adopt Lean Manufacturing and Six Sigma strategies, particularly in enhancing quality control and reducing waste and process variability.